Uric acid alterations by consumption of gluten-free bakery products in relation to cardiovascular and metabolic syndrome risk factors - Martina Gažarová; Lucia Mečiarová (National Institute of Public Health - National Institute of Hygiene, 2020)
Background. Serum uric acid (UA) levels are one of the determinants of the cardiovascular disease and metabolic syndrome but none of criteria for that syndrome include serum UA. Consumption of bakery products (with or without gluten) is associated with an increasing prevalence of overweight/obesity and hyperuricemia frequently occurs in subjects with overweight and obesity. Objective. The aim of the study was to find out how 6-weeks consumption of gluten-free bakery products can affect risk factors for cardiovascular disease and metabolic syndrome, and especially uric acid levels. Material and Methods. The group was composed of 27 female volunteers consuming gluten-free bakery products during 6-week period. The biochemical parameters levels were measured by Biolis 24i Premium, the anthropometric parameters by InBody 720 and blood pressure by OMRON Microlife. Results. We found a non-significant increase in total cholesterol and decrease in triglycerides, in the case of LDL cholesterol a significant reduction in values and increase of HDL cholesterol. Glucose level increased significantly, but uric acid has not changed significantly. We found the highest total cholesterol, triglyceride, and LDL concentrations in the third UA quartile. The highest glucose concentrations were found in the lower UA quartiles, while the lowest in the highest quartiles. Linear increases in UA concentrations were not observed in any of the parameters. Evaluation of the anthropometric parameters showed that while values of BMI, VFA, fat mass and waist circumference were the highest at the beginning of the study in the second quartile, after intervention the highest values were shifted to the third quartile. Conclusions. Due to the consumption of gluten-free bakery products the risk values of the monitored parameters shifted to higher UA quartiles.